2022
DOI: 10.1111/1759-7714.14342
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin resistance and malignant behaviors of lung cancer cells are promoted by circ_0002360 via targeting miR‐6751‐3p to regulate the expression of ZNF300

Abstract: Background: Circular RNAs (circRNAs) are key regulators in oncogenesis and chemoresistance of human cancers. Herein, we focused on the roles of circ_0002360 in regulating lung cancer progression and cisplatin (DDP) resistance. Methods: The detection of circ_0002360, microRNA-6751-3p (miR-6751-3p) and zinc finger protein 300 (ZNF300) was conducted via reverse transcription-quantitative polymerase chain reaction assay. Cell sensitivity was determined using cell counting kit-8 assay. Proliferation detection was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Circ_0002360 can function as a potent oncogenic promoter in NSCLC by elevating the expression of matrix metalloproteinase 16 (MMP16) by sponging multiple miRNAs [ 14 ]. Moreover, circ_0002360 accelerates the cisplatin resistance and malignant phenotypes of lung cancer cells through the miR-6751-3p/ZNF300 axis [ 15 ]. In this work, our data found that circ_0002360 was evidently overexpressed in Taxol-resistant NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circ_0002360 can function as a potent oncogenic promoter in NSCLC by elevating the expression of matrix metalloproteinase 16 (MMP16) by sponging multiple miRNAs [ 14 ]. Moreover, circ_0002360 accelerates the cisplatin resistance and malignant phenotypes of lung cancer cells through the miR-6751-3p/ZNF300 axis [ 15 ]. In this work, our data found that circ_0002360 was evidently overexpressed in Taxol-resistant NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Human circ_0002360, generated by the back-spliced exons of RUNX family transcription factor 1 (RUNX1), is highly expressed in NSCLC and operates as a promoter in NSCLC [ 13 , 14 ]. Moreover, circ_0002360 can contribute to the cisplatin resistance and malignant phenotypes of lung cancer cells by upregulating zinc finger protein 300 (ZNF300) through miR-6751-3p competition [ 15 ]. However, no studies proved the function of circ_0002360 in the Taxol resistance of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The high abundance, stability, and conservation of circRNAs make them advantageous as diagnostic markers ( 37 ). It has been reported that hsa_circ_0002360 is highly expressed in NSCLC tissues and contributes to the malignant behavior of NSCLC ( 38 40 ). Circulating hsa_circ_0001953 can be used as a marker for proliferative diabetic retinopathy and active tuberculosis, which have not been investigated in cancer ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%